The efficacy and safety of Xiao-Ban-Xia-Tang in the treatment of chemotherapy-induced nausea and vomiting: A systematic review and meta-analysis - Li, Ling; Jia, Shangmei; Yu, Chenghao; Shi, Shasha; Peng, Fu (Frontiers in Pharmacology, 2024)
Chemotherapy-induced nausea and vomiting (CINV) is one of the most frequent and critical side effect due to chemotherapeutics. In China, Xiao-Ban-Xia-Tang (XBXT) has been already applied extensively to prevent and treat CINV. However, there is limited testimony on the effectiveness and safety of this purpose, and there was no correlative systematic review. This review aims to systematically evaluate the effectiveness and safety of XBXT in preventing and treating CINV. Methods The systematic search was conducted in eight databases to acquire randomized controlled trials (RCTs) that appraised the effect of XBXT in treating CINV. The vomiting and nausea relief efficiency, eating efficiency, quality of life, and adverse reactions were explored for efficacy assessment. Bias risk was rated by manipulating the Cochrane risk of bias tool 2.0 (RoB 2). The retrieved investigations were analyzed by utilizing the Review Manager 5.4 and Stata 17.0. The quality of evidence was evaluated adopting the GRADE tool. Results A total of 16 clinical RCTs of XBXT in the treatment of CINV were incorporated into the investigation, with a total of 1246 participants. The meta-analysis showed that compared with conventional antiemetic drugs, XBXT and antiemetics improved the vomiting relief efficiency (RR 1.35, 95% confidence interval: 1.25-1.46, P < 0.00001), nausea relief efficiency (N = 367, RR 1.23, 95% CI: 1.09-1.38, P < 0.00001), quality of life (RR = 1.37, 95% CI: 1.14-1.65, P = 0.0009), and reduced the adverse events (N = 370, RR 0.53, 95% CI: 0.29-0.96, P = 0.04). XBXT and DARAs raised eating efficiency compared with DARAs (N = 208, RR 1.30, 95% CI: 1.07 - 1.57, P = 0.007). The data existed as statistically significant, and the publication bias was identified as relatively low from funnel plot and trim and fill analysis. Besides sensitivity analysis demonstrated robust outcomes. The quality of evidence for each outcome ranged from moderate to high.